2019
DOI: 10.15416/ijcp.2019.8.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Antimicrobial Stewardship Program di Kawasan Asia: Sebuah Kajian Sistematis

Abstract: AbstrakAntimicrobial Stewardship Program (ASP) merupakan salah satu program yang direkomendasikan untuk meningkatkan ketepatan penggunaan antibiotik, khususnya pada setting rumah sakit. Keberhasilan implementasi program tersebut ditentukan oleh banyak faktor, antara lain komunikasi antartenaga kesehatan dan ketersediaan sumber daya manusia maupun sarana-prasarana. Sampai saat ini, bukti penelitian terkait implementasi ASP di Asia, khususnya di negara low-dan lower-middle-income economies, masih terbatas. Tujua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…9 One of irrational use of antibiotics is the excessive use of broad-spectrum antibiotics. 10 Studies conducted by Sidabutar et al and Marra et al showed an increase in the use of Amoxicillin which is a broad-spectrum antibiotic for tooth extraction. 11,12 Another study conducted by Choi et al showed that the use of broad-spectrum postextraction antibiotics was given to patients without systemic disease compared to patients with systemic disease.…”
Section: Introductionmentioning
confidence: 99%
“…9 One of irrational use of antibiotics is the excessive use of broad-spectrum antibiotics. 10 Studies conducted by Sidabutar et al and Marra et al showed an increase in the use of Amoxicillin which is a broad-spectrum antibiotic for tooth extraction. 11,12 Another study conducted by Choi et al showed that the use of broad-spectrum postextraction antibiotics was given to patients without systemic disease compared to patients with systemic disease.…”
Section: Introductionmentioning
confidence: 99%